Narsisme, Religiusitas dan Penggelapan Pajak - Ar Rezzy, Muhamad Fazra; Helmy, Herlina (Jurnal Eksplorasi Akuntansi, 2025)
This research aims to investigate the influence of narcissism, moderated by religiosity, on tax evasion among taxpayers in Padang City. The study employed simple random sampling, with 400 respondents participating. Primary data was collected through a survey using direct distribution of questionnaires. Data analysis utilized moderated regression analysis (MRA) through spss 26. The findings reveal that (1) narcissism positively influences tax evasion significantly, and (2) religiosity significantly moderates the relationship between narcissism and tax evasion, exhibiting a negative effect.